2010
DOI: 10.1095/biolreprod.109.082206
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Cumulus-Denuded Oocytes Restore Developmental Capacity Completely When Matured with Optimal Supplementation of Cysteamine, Cystine, and Cumulus Cells1

Abstract: Our objectives were to study how cysteamine, cystine, and cumulus cells (CCs), as well as oocytes interact to increase oocyte intracellular glutathione (GSH) and thereby to establish an efficient in vitro maturation system for cumulus-denuded oocytes (DOs). Using M16 that contained no thiol as maturation medium, we showed that when supplemented alone, neither cystine nor cysteamine promoted GSH synthesis of mouse DOs, but they did when used together. Although goat CCs required either cysteamine or cystine to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 88 publications
2
20
0
1
Order By: Relevance
“…Oocyte activation, IVF, and embryo culture Procedures followed for oocyte activation, IVF, and embryo culture were exactly those reported by Zhou et al (2010), except that zona drilling was not carried out before insemination in this study. Blastocysts obtained were either stained with Hoechst 33342 for cell counting or transferred into surrogate mothers to observe postimplantation development.…”
Section: Oocyte Recovery and In Vitro Maturationmentioning
confidence: 83%
See 1 more Smart Citation
“…Oocyte activation, IVF, and embryo culture Procedures followed for oocyte activation, IVF, and embryo culture were exactly those reported by Zhou et al (2010), except that zona drilling was not carried out before insemination in this study. Blastocysts obtained were either stained with Hoechst 33342 for cell counting or transferred into surrogate mothers to observe postimplantation development.…”
Section: Oocyte Recovery and In Vitro Maturationmentioning
confidence: 83%
“…In vitro, however, the synthesis of glutathione may be impaired because of a deficiency of cysteine in the culture medium and its high instability and easy auto-oxidation to cystine (Bannai 1984, Sagara et al 1993. Furthermore, our previous study has shown that neither mouse cumulus cells nor the oocyte itself could use cystine or cysteamine when added alone, but cysteamine could reduce cystine to cysteine in a cell-free medium (Zhou et al 2010). Therefore, cystine and cysteamine were used in combination in this study to promote the synthesis of glutathione in oocytes from restraint-stressed mice.…”
Section: Cc-cc+mentioning
confidence: 99%
“…in many mammalian species including mouse (Zhou et al 2010), bovine (Assidi et al 2008), and human (Russell & Robker 2007, Anderson et al 2009). Keeping in mind that most of the transcriptional activity of the oocyte occurred during meiotic arrest before the GVBD (Hyttel et al 2001), the study of the CCs gene expression patterns at the GVBD stage (6 h post-LH) could reflect the oocyte's quality.…”
Section: Study Approachmentioning
confidence: 99%
“…Because glutathione derived from GCs and CCs is required for sperm decondensation and male pronucleus formation, lack of ability to produce glutathione in DOs restrains their development (Perreault et al 1988, Zhou et al 2008, 2010. Hence, when DOs are co-cultured with GC monolayer during IVM, glutathione levels are restored and developmental competence is reestablished (Zhou et al 2008(Zhou et al , 2010. Normal growth and maturation of the oocyte is thus a direct reflection of physiological status of the GCs.…”
Section: Introductionmentioning
confidence: 99%